BIOLOGY AND BIOTECHNOLOGY OF ENDOPHITE MICROORGANISMS - Makhmudova Zakro Vahobovna; Shodiyeva Dildora; Olimjonova Sadokat Gulomjon's daughter. (Scholar Express Journals, 2023)
Today, endophytic microorganisms are widely studied around the world, and scientists have collected a lot of information about it. The role and properties of endophytic microorganisms in the growth and development of plants are of great practical importance. In particular, endophytic microorganisms were first described by the German botanist John Link in 1809. Although its role in plants was unknown at first, later French scientist Beecham proposed to call it "microorganism", and finally in 1887, Victor Galipp discovered bacteria found in plant tissues. Endophytic microorganisms, like other biological concepts, are based on many scientific studies that have been confirmed over time. The term "endophyte" means "endo" means inside and "phyton" means plant.
Keywords: Endophyte; endophytic archaea; viruses; viroids